Asserting State Sovereignty over National Communities of Islam in the United States and Britain: Sharia Courts as a Tool of Muslim Accomodation and Integration - Christopher R. Lepore (Washington University Global Studies Law Review, 2012)
This Note considers whether the United States should follow Britain‘s example by explicitly sanctioning sharia courts for private arbitrations. Moreover, it looks more broadly to the role, if any, that sharia law should have in domestic courts across the country. In doing so, it argues the United States should learn from Britain‘s example because, with proper procedural safeguards, parties could use sharia courts in limited circumstances as an effective tool in alternative dispute resolution. Perhaps more importantly, it further suggests that sharia courts could offer a useful mechanism for the United States to manage the challenges posed by transnational Islam.
Keywords: state sovereignty; United States; Great Britain; Muslim; Sharia courts